DAMPAK POLITIK ETIS TERHADAP PERGERAKAN KEBANGSAAN DI KALIMANTAN SELATAN - Wajidi, Wajidi (Puslitjakdikbud Balitbang Kemdikbud, 2016)
AbstractThe national movements in South Kalimantan is the impact of Europe’s political andcultural penetration of the East Indies Government. The powerful impact of penetrationwas education that bring in the modern educated elite. Therefore, the issues that is raisedin this paper, i.e.: (1) How Ethical policy of East Indies government?; (2) How aregovernment policies for education and the emersion of modern elite?; (3) How is the roleof modern elite to emergence of the nationalist movement in South Kalimantan, Indonesia?This study uses historical (Historical Research) by using heuristic step, criticism,interpretation and historiography. The method of this article is historical research thatuses heuristic, critic, interpretation, and historiography. The results show that the ethicalpolitics was motivated by the criticism that the Netherland-Indies government woulddo “returning the favor” towards the Indonesian people with the slogan, “Irrigation,Education and Emigration”. Through a policy in education, schools was built to createlow-level workers with western paradigm. Those who attended these school were theones, upon their returning home, became the pioneers and driving the movements orspreading the seeds of nationality in South Kalimantan. AbstractTumbuhnya pergerakan kebangsaan di Kalimantan Selatan merupakan dampakdari penetrasi politik dan kebudayaan Eropa pada masa Pemerintahan Hindia Belanda.Penetrasi yang sangat kuat pengaruhnya adalah bidang pendidikan yang melahirkanelit modern yang terpelajar. Oleh karena itu permasalahan yang diangkat dalam tulisanini adalah: (1) Bagaimana kebijakan Politik Etis di Hindia Belanda?; (2) Bagaimanakebijakan Pemerintah Hindia Belanda di bidang pendidikan dan munculnya elite modern?;(3) Bagaimana peranan elite modern terhadap munculnya pergerakan kebangsaanIndonesia di Kalimantan Selatan? Penelitian ini menggunakan metode sejarah (HistoricalResearch) dengan menggunakan langkah heuristik, kritik, interpretasi dan historiografi.Hasil penelitian menunjukkan bahwa politik etis didorong oleh kiritik bahwa pemerintahHindia Belanda harus melakukan “balas budi” pada rakyat Indonesia dengan slogan“Irigasi, Edukasi dan Emigrasi”. Melalui kebijakan di bidang pendidikan, sekolahdimaksudkan untuk mencetak pegawai rendahan dengan pendidikan Barat. Merekayang telah mengenyam pendidikan adalah kalangan terpelajar atau kaum cendekiawanyang kembali ke kampung halaman dan turut menjadi pelopor atau penggerak organisasipergerakan kebangsaan dan menanamkan benih kebangsaan di Kalimantan Selatan.